2007
DOI: 10.1111/j.1745-6584.2006.00277.x
|View full text |Cite
|
Sign up to set email alerts
|

Seepage Face Height, Water Table Position, and Well Efficiency at Steady State

Abstract: When a fully penetrating well pumps an ideal unconfined aquifer at steady state, the water table usually does not join the water level in the well. There is a seepage face inside the well, which is a key element in evaluating the well performance. This problem is analyzed using the finite-element method, solving the complete equations for saturated and unsaturated flow. The seepage face position is found to be almost independent of the unsaturated zone properties. The numerical results are used to test the val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…Many simulated and observed results have reported the existence of a seepage face and its effects on water flow and solute transport (Vachaud et al, 1973;Simpson et al, 2003;Rushton, 2006;Chenaf and Chapuis, 2007). For example, in a sand box experiment involving radial flow and transport, Simpson et al (2003) found that the flow velocity through the seepage face was about 30% higher than at the base of the aquifer, while the solute transport patterns were strongly influenced by the flow characteristics of the system.…”
Section: Seepage Facementioning
confidence: 99%
“…Many simulated and observed results have reported the existence of a seepage face and its effects on water flow and solute transport (Vachaud et al, 1973;Simpson et al, 2003;Rushton, 2006;Chenaf and Chapuis, 2007). For example, in a sand box experiment involving radial flow and transport, Simpson et al (2003) found that the flow velocity through the seepage face was about 30% higher than at the base of the aquifer, while the solute transport patterns were strongly influenced by the flow characteristics of the system.…”
Section: Seepage Facementioning
confidence: 99%
“…An essential feature of an agrowell is the formation of a seepage face (Fig. 5(b)) between the water table at the edge of the well and the pumped water level (Simpson et al, 2003;Rushton, 2006;Chenaf and Chapuis, 2007). This is represented in the groundwater model by modifying the hydraulic conductivity for the four grid lines connected to the well by a factor of 0.28; this factor was adjusted for best-fit.…”
Section: Appendix a Information And Parameters For Computational Modelsmentioning
confidence: 99%
“…Several authors developed purpose-specific numerical models (e.g. Cooley and Cunningham 1979;Kaleris et al 1995;Von Hofe and Helweg 1998;Rushton 2006;Chenaf and Chapuis 2007), while others relied on commercially available groundwater modeling programs, such as MODFLOW (e.g. Barrash et al 2006;Horn and Harter 2009;Houben and Hauschild 2011;McMillan et al 2014), FEFLOW (Rubbert and Treskatis 2008) and HYDRUS-2D (Yakirevitch et al 2010).…”
Section: Transient Flow To Wellsmentioning
confidence: 99%
“…The red bar shows the area suitable for the linear approximation (Eq. 51) proposed by Parsons (1994) and Rushton 1989;Rushton 2006;Chenaf and Chapuis 2007;Yakirevitch et al 2010;Behrooz-Koohenjani et al 2011).…”
Section: Seepage Face In Unconfined Aquifersmentioning
confidence: 99%
See 1 more Smart Citation